2020
DOI: 10.1101/2020.09.28.316687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterization of RIGI, TLR7 and TLR3 as immune response gene of indigenous ducks in response to Avian influenza

Abstract: Avian influenza is an alarming disease, which has every possibility to evolve as human to human pandemic situation due to frequent mutation and genetic reassortment or recombination of Avian influenza(AI) virus. The greatest concern is that till date no satisfactory medicine or vaccines are available, leading to massive culling of poultry birds causing huge economic loss, and ban on export of chicken products, which emphasise the need develop alternative strategy for control of AI. In the current study we atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In our earlier study, we observed that RIGI was better expressed in avian influenza (of H5N1 strain) virus infected ducks in comparison to healthy control (Pal et al, 2021). It is to be noted that avian influenza virus is a RNA virus, whereas duck plague virus is a DNA virus.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our earlier study, we observed that RIGI was better expressed in avian influenza (of H5N1 strain) virus infected ducks in comparison to healthy control (Pal et al, 2021). It is to be noted that avian influenza virus is a RNA virus, whereas duck plague virus is a DNA virus.…”
Section: Discussionmentioning
confidence: 89%
“…In the current study we proposed to study the molecular pathogenesis of different body organs including gut and other organs which are affected by duck plague virus. In our lab, we had already studied the effect of immune response genes against avian influenza, whose genome content is RNA (Pal et al, 2021). Here we attempt to study immune responsiveness against DNA virus as Duck plague virus.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that ducks have a unique feature of better resistance to commonly occuring avian diseases. A remarkable feature of indigenous ducks has been observed that they are even better resistant to avian influenza virus with explored molecular basis 1 . Immune response genes were identified in Bengal duck providing host resistance against duck plague 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In fibroblasts, platelet-derived growth factor stimulation induces sustained promotes S-phase entry and ERK activation 26-30 . Earlier in our lab, we have characterized certain immune response genes in Anas platyrynchos(Bengal duck) 31-37 .…”
Section: Introductionmentioning
confidence: 99%
“…Ducks were observed to be mostly forager with better disease resistance (Pal et al, 2021), higher adaptability and hardy breed (Pal, A. 2020, Pal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%